Using the Properties of Equality, fill the blanks with the correct value to show the solution for y . 3(y - 2) = 18
y(3(y-2))=18 y(3y-6)=18 3y^2-6y=18 3y^2-6y-18=0 find the zero(s) use quadratic formula
@darkknight ATTENTION please !!!! the correct equation from there above is 3(y-2) = 18 check - reread - please the text of this problem - ty.
oh sorry, wth where are the blanks in that? anyways in that case you have 3(y-2)=18. The property of equality is when both sides of the EQN have the same solution. so you can distribute the 3 so its 3y-6=18. Add 6 to both sides then divide by 3. Also @jhonyy9 u can chill